Pigment epithelial-derived factor in human fetal membranes - Stalberg, Cecilia; Noda, Nathalia [UNESP]; Polettini, Jossimara [UNESP]; Jacobson, Bo; Menon, Ramkumar (Taylor & Francis, 2018)
Objective: Our main objective was to document, pigment epithelial-derived factor (PEDF), a secreted serine protease inhibitor with anti-angiogenic, anti-inflammatory, and anti-oxidant properties, expression in human fetal membranes from preterm prelabor rupture of the membranes (pPROM) and in in vitro cultures stimulated with cigarette smoke extract (CSE) or lipopolysaccharides (LPS), two major risk factors for pPROM (behavioral and bacterial, respectively). Method: We documented PEDF mRNA expression in clinical samples of fetal membranes from patients with pPROM using quantitative RT-PCR. Also, mRNA and protein levels were documented in fetal membranes (from normal term cesarean sections [not in labor]) in an organ explant system stimulated with CSE or lipopolysaccharide (LPS). Immunohistochemistry (IHC) was used to localize PEDF in fetal membranes. Results: We report no changes in PEDF mRNA expression in pPROM compared to term births (p =.59) or after treatment with CSE or LPS. However, by adding sulforaphane the PEDF mRNA expression increased significantly p <.000032. PEDF was localized to both amnion and chorion layers, but no difference was seen in staining intensities after CSE or LPS treatment compared to control. Conclusions: PEDF, a product of fetal membrane cells, is unaltered in pPROM or after exposure to risk factors of pPROM. The antioxidant stimulating substance sulforaphane contribute to an increase in PEDF mRNA in fetal membranes.
Keywords: bacterial infection; fetal membrane; pPROM; Serpinf1; smoking